Crohn's disease and colorectal cancer. Issue 5 (May 1994) - Gillen, C D; Andrews, H A; Prior, P; Allan, R N
Abstract : The colorectal cancer risk in Crohn's disease eliminating all known biases was assessed in a cohort of 281 patients with Crohn's disease who resided in the West Midlands at the time of diagnosis, and were first seen within five years of onset of symptoms between 1945-1975. All patients were 15 years of age or more at onset and were followed up from 12-35 years (total 5213 person years at risk (PYR)). The colorectal cancer risk in the series compared with the risk in the general population was computed by applying sex and age specific PYRs to the date of death or end of the study period 31 December 1991. There were six colonic and two rectal cancers. Six of the eight colorectal cancers were diagnosed 20 or more years after the onset of Crohn's disease. The relative risk (RR) of colorectal cancer for the series as a whole was 3.4 (p < 0.001), with a fivefold excess in the colon, but no significant excess in the rectum. Patients with extensive colitis showed an 18-fold increase in risk (RR = 18.2, p < 0.001), which decreased with increasing age at onset. This study shows that there is a statistical excess risk of developing colorectal cancer in patients who develop their Crohn's disease at a young age of onset (less than 30 years of age).